(untitled) (Proceedings of the International Conference on Public Health, 2022)
The Community Health Education Initiative, inspired by a needs assessment conducted in Uttar Pradesh, aimed to improve health education in a rural community by addressing pertinent health topics. The primary focus was to create a self-sustainable model in which local Women Educational Leaders (WELs) were trained by the research team to educate their village on chosen health topics. A pilot study was conducted among the high-school girls of Pardada Pardadi Educational Society. Our research team curated and administered a multiple-choice questionnaire (A1) to assess baseline knowledge, taught the material using educational handouts, and then administered the same questionnaire (A2). There was a statistically significant improvement between A1 and A2, demonstrating internal validity. This same initiative was then attempted among the villagers with the WELs as educators and there was no statistically significant improvement between A1 and A2, indicating poor knowledge retention of the learned health topics. We believe this initiative’s effectiveness in the village was impacted by multiple elements. Many villagers were unable to read/write Hindi, rendering educational materials ineffective. In the future, utilizing pictorials and oral storytelling would likely be more effective. The WELs were also uncomfortable teaching the men given the traditional gender roles present in this society. One solution would be to reform WEL training to overcome this barrier. It is important to recognize that despite how thorough the creation of a multi-perspective program may be in theory, there will always be unanticipated variables that can influence effectiveness. These ‘lessons learnt’ from the field will not only aid consecutive phases of this project but will also serve as a model for investigators pursuing similar endeavors in rural health education.